Interrelation of proepicardium, proepicardium-like structures and septum transversum on early stages of prenatal ontogenesis of Cobb 500 hens - Pototskaya O.Yu. (Морфологія, 2009)
Proepicardium is multipotential temporal embryonic structure wich is the source of many cellular populations of heart, but derivation of some of them is still under debate. In understanding of this problem it is very important to imagine interconnections between proepicardium and neighbor mesenchymal structures, such as septum transversum and proepicardium-like structures. Thus, the goal of our research was to reveal interconnection between abovementioned elements; to describe the features of septum transversum and proepicardium-like structures in birds. We used Cobb 500 chick embryos as a material; on the basis of pictures of serial sections, with the help of Photoshop CS2, Amira for microscopy 5.0, 3ds max 8.0 computer programs, three-dimensional models of proepicardium, proepicardium-like structures, heart and septum transversum on 17 stage of development by Hamburger-Hamilton (HH) were made. Proepicardium-like structures, beginning from 16 stage by HH, were connected with proepicardium, septum transversum and, from 17 stage by HH, - with mesenchyme of right body wall. Proepicardium-like structures and septum transversum appeared as symmetrically structures, but their right components developed more actively. On the 17 stage by HH in apical part of septum transversum it were observed apoptotic cells; on the same stage in the basis of proepicardium was situated the liver bud. Sometimes, from 14 to 17 stages by HH, in septum transversum localized blood islands.